Advanced Listening Comprehension : Developing Listening and Note - Taking Skills - Dunkel, Patricial (TP.HCM, 2004)
This book is a program for high-intermediate and advanced students of English as a second language who seek to improve their listening comprehension of English and their note - taking skills. Fifteen lectures guides the students along in this endeavvor. Aside from developing note - taking ability, several other interloking skills necessary for academic sucess are worked on in tandem: 1. Processing information received aurally; 2. Making inferences and drawing conclusions therefrom; 3. Becoming familiar with the various styles and accents of lectures; 4. handing objective test-taking formals and 5. preparing for classroom discussion and debates....